From cognitive and behavioral impairment to clinical trial inclusion, for an inclusive approach of amyotrophic lateral sclerosis - Juliette Foucher (2025)
ALS is a fatal and rapidly progressing neurodegenerative disease where the death of motor neurons results in the paresis of skeletal muscles and ultimately death from respiratory failure within 2 to 5 years. As no cures are currently available, people living with ALS (pALS) rely on clinical trials. However, the design of ALS trials does not always reflect the vast heterogeneity of the disease. Most pALS with behavioral or cognitive impairment are excluded from ALS trials, and many patients with bulbar ALS are struggling to perform some tests including in trial screening visits. In this thesis, we aimed to characterize cognitive and/or behavioral impairment of pALS in Sweden and use our findings as a stepping- stone to investigate clinical trial inclusiveness in a broader sense, with a focus on pre-screening and screening.In Study I, we conducted a systematic review on the use of population and disease registries for clinical trial pre-screening. Our goal with this study was to set the stage for what is currently done and learn from previous research. Therefore, we did not limit our search to the ALS field but included all publications from 2014 to 2022 reporting registry use of trial pre-screening. We found that during that timeframe, only 24 studies clearly reported such use despite obvious benefits being stated such as time efficiency of the pre-screening time and economic benefits. Pre-screening strategies being under-reported in the scientific literature, more population or disease registries may be used in a trial recruitment setting, however it seems like the clinical trial world is heavily relying on recruitment registries specifically designed for trial recruitment purposes.In Study II, we aimed to validate the Swedish version of the Edinburgh Cognitive and Behavioral ALS Screen (ECAS), a screening tool for cognitive impairment. We found that the Swedish version of the ECAS was a valid and reliable tool to use, which led us to investigate cognition of pALS longitudinally, using the ECAS in Study III. We found that cognition was stable in pALS during the first 2 years following the ALS diagnosis, and we identified 3 main clusters of cognitive impairment profiles.In Study IV, we aimed to translate and implement the dimensional apathy scale (DAS) in Swedish within our cohort, characterize the apathy levels of pALS and investigate their longitudinal apathy levels. We found that the DAS was reliable to use in Swedish, that emotional and executive apathy levels were stable during the first year following the ALS diagnosis, but we did not observe a statistically significant relationship between apathy levels and clinical trial interest.Finally in Study V, we investigated venous bicarbonate as a potential proxy to vital capacity as a trial eligibility criterion. We found that venous bicarbonate was able to predict survival. Moreover, venous bicarbonate concentrations over 26 mmol/L were associated with higher risks of death for pALS.In summary, cognitive impairment and apathy levels in Swedish pALS were characterized in this thesis. Additional studies are required to investigate potential apathy clusters or profiles in pALS, as well as discriminative predictors for trial participation and considerations.List of scientific papersI. Foucher, J., Azizi, L., Öijerstedt, L., Kläppe, U., & Ingre, C. (2024). The usage of population and disease registries as pre-screening tools for clinical trials, a systematic review. Systematic Reviews, 13(1), 111. https://doi.org/10.1186/s13643-024-02533-0II. Foucher, J., Winroth, I., Lovik, A., Sennfält, S., Pereira, J. B., Fang, F., Lule, D., Andersen, P. M., & Ingre, C. (2023). Validity and reliability measures of the Swedish Karolinska version of the Edinburgh Cognitive and Behavioral ALS Screen (SK-ECAS). Amyotrophic Lateral Sclerosis & Frontotemporal Degeneration, 1-6. Advance online publication. https://doi.org/10.1080/21678421.2023.2239857III. Öijerstedt, L., Foucher, J., Lovik, A., Yazdani, S., Juto, A., Kläppe, U., Fang, F., & Ingre, C. (2024). Repeated cognitive assessments show stable function over time in patients with ALS. Journal of Neurology, 271(8), 5267-5274. https://doi.org/10.1007/s00415-024-12479-xIV. Foucher, J., Lovik, A., Öijerstedt, L., Radakovic, R., Fang, F. & Ingre, C. Longitudinal apathy measures show stability of executive and emotional apathy levels but no association between apathy levels and clinical trial interest. [Manuscript]V. Foucher, J .* , Wellander, T .* , Lovik, A., Öijerstedt, L., Juto, A., Fang, F., & Ingre, C. Venous bicarbonate, a proposed proxy for vital capacity to be used as an eligibility criterion in amyotrophic lateral sclerosis clinical trials. [Submitted]* Equal contribution